127k views
1 vote
Please explain your answer. THX!!!!

Please explain your answer. THX!!!!-example-1
Please explain your answer. THX!!!!-example-1
Please explain your answer. THX!!!!-example-2
User Dzl
by
5.5k points

1 Answer

4 votes

Answer:

1)
cos(x)sin^(2)x

2)0

Explanation:

for part 1:

Given cos(x) - cos^3(x)

= cos(x) (1- cos^2(x))

Using the identity
cos^(2)x +sin^(2)x=1\\ sin^(2)x=1-cos^(2)x

= cos(x)sin^2(x)

for part 2:

given

=
cos(5\pi )/(8)cos(\pi )/(8)  + sin(5\pi )/(8)sin(\pi )/(8)

Using the identity cos(a)cos(b) + sin(a)sin(b)= cos(a-b)

=
cos((5\pi )/(8) -(\pi )/(8))

=
cos(4\pi )/(8)

=
cos(\pi )/(2)

=0!

User Mindeh
by
4.9k points